Processamento auditivo e migrânea com e sem componente vestibular: estudo comportamental e eletrofisiológico em adultos - Agessi, Larissa Mendonca [UNIFESP] (2019)
Introduction: Migraine could change the thickness and the functioning of the temporal lobe, where the last station of the auditory pathway in the cortex is located. Therefore, identifying changes in auditory behavior and auditory evoked potentials of individuals with migraine may help to understand the effects of this disease on the central auditory nervous system. Objective: To analyze auditory abilities and auditory evoked potentials in adults diagnosed with vestibular migraine, migraine with and without aura, and to compare them with adults without headache. Method: Forty-three volunteers were divided into three groups: - Vestibular migraine (MV): 13 individuals (12 women and 1 man) with vestibular migraine, with mean values: 24.31 years old, 6.62 days of headache per month and 13.23 years of disease time; - Migraine group with and without aura (MwA e MA): 15 individuals with migraine with and without aura (13 women and 2 men), with mean values: 26.67 years old, 7.67 days of headache per month, 13.33 time of illness; - Control group (GC): 15 individuals (13 women and 2 men), with mean values of 24.33 years old, without headache. Participants of the MV and MwA e MA groups were diagnosed according to the International Headache Society (ICHD-III, 2013). The exclusion criteria consisted of: psychiatric or other neurological diseases, head trauma, hearing loss, use of ototoxic drugs, chronic migraine and use of preventive medication for migraine or affecting the central nervous system. The eligibility procedures of the sample were: anamnesis, pure tone audiometry, and measures of acoustic immittance. The procedures applied were: the evaluation of the temporal resolution ability in noise segment (GIN), evaluation of the temporal ordering with the Pure Tone Pattern Test (TPD), evaluation of the figure-ground ability for listening verbal sounds with syllables (TDCV) and words (SSW), and electrophysiological evaluation using the click ABR and P300." Results: There were no significant differences for the variables age, education level, and gender among the three groups. There were no significant differences between groups with migraine for the variables: days of headache per month and mean time of disease. The sample consisted of individuals with auditory thresholds, tympanometry and normal acoustic reflexes; however, in the statistical analysis, increased auditory thresholds were identified in the groups with migraine. In the study of ordering and temporal resolution abilities, statistically significant results were identified for worse performance for the groups with migraine in relation to the control group. The figure-ground ability was similar among the three groups. In the electrophysiological evaluation, there was a statistically significant results found for worse performance in the MwA e MA group for the P300 right ear amplitude and latency in relation to the control group. The latency measurements of the click ABR were similar for statistical analysis between the groups, however, 3 individuals from the MV group and 7 from the MwA e MA group obtained alterations. Conclusions: The auditory temporal processing showed a disfunction in the neurological processing of auditory information regarding the abilities of resolution and temporal ordering of short and successive sounds that differ in their duration. Long latency potentials showed decreased processing speed and reduced attention to stimulation in individuals with migraine with and without aura compared to the group without headache. The profile of the auditory abilities evaluated, and the auditory evoked potentials did not differentiate the groups with and without the vestibular component. It is concluded, therefore, that the auditory evaluation could help the neurological diagnosis and the intervention of patients with migraine.